1994
DOI: 10.1111/j.1365-2958.1994.tb00312.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the mutX gene of Streptococcus pneumoniae as a homologue of Escherichia coli mutT, and tentative definition of a catalytic domain of the dGTP pyrophosphohydroiases

Abstract: We show that deletion of a gene of Streptococcus pneumoniae, which we call mutX, confers a mutator phenotype to resistance to streptomycin. Analysis of the DNA sequence changes that occurred in several streptomycin-resistant mutants showed that mutations are unidirectional AT to CG transversions. The mutX gene is located immediately downstream of the previously identified ung gene and genetic evidence suggests that the two genes are co-ordinately regulated. Nucleotide sequence determination reveals that the mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
72
0

Year Published

1994
1994
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(74 citation statements)
references
References 41 publications
2
72
0
Order By: Relevance
“…A modified polyethyleneimine-cellulose TLC was used to develop the reaction products in 0.75 M LiCl. We found that this running buffer resolved m 7 GDP from 32 Pi, which otherwise comigrate in the standard 0.45 M (NH 4 ) 2 SO 4 buffer (18). As shown in Fig.…”
Section: Resultsmentioning
confidence: 75%
See 2 more Smart Citations
“…A modified polyethyleneimine-cellulose TLC was used to develop the reaction products in 0.75 M LiCl. We found that this running buffer resolved m 7 GDP from 32 Pi, which otherwise comigrate in the standard 0.45 M (NH 4 ) 2 SO 4 buffer (18). As shown in Fig.…”
Section: Resultsmentioning
confidence: 75%
“…The Nudix motif was originally identified in a class of pyrophosphatase proteins and shown to be critical for pyrophosphatase activity (31,32). The Nudix motif consists of a highly conserved 23-aa sequence, GX 5 EX 7 REUXEEXGU, where X can be any amino acid and U is an aliphatic hydrophobic amino acid (31,32). To test whether the hDcp2 Nudix motif was functional, the two conserved glutamic acid residues (E147 and E148) within this motif were substituted by glutamine.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Genes for MutT homolog proteins with dGTPase or 8-oxodGTPase activity were identified in Proteus vulgaris and Streptococcus pneumoniae, bacteria distantly related to E. coli (16,17). All three MutT homolog proteins have molecular masses ranging from 13 to 18 kDa, and the degree of identity ranges from 19 to 40%.…”
mentioning
confidence: 99%
“…This motif was first described as a MutT motif in a MutT protein from Escherichia coli (2). MutT is a nucleoside triphosphatase that hydrolyzes all canonical nucleoside triphosphates with a preference for deoxyguanosine triphosphate (dGTP) and its oxidized form 7,8-dihydro-8-oxodeoxyguanosine .…”
mentioning
confidence: 99%